Determining the Minimal Important Change of Everyday Functioning in Dementia: Pursuing Clinical Meaningfulness. (30th August 2022) - Dubbelman, Mark A.; Verrijp, Merike; Terwee, Caroline B.; Jutten, Roos J.; Postema, Merel C.; Barkhof, Frederik; Berckel, Bart N.M.; Gillissen, Freek; Teeuwen, Vivianne; Teunissen, Charlotte; van de Flier, Wiesje M.; Scheltens, Philip; et al.
Abstract : Background and Objectives: Decline in everyday functioning is a key clinical change in Alzheimer disease and related disorders (ADRD). An important challenge remains the determination of what constitutes a clinically meaningful change in everyday functioning. We aimed to investigate this by establishing the minimal important change (MIC): the smallest amount of change that has a meaningful effect on patients' lives. We retrospectively investigated meaningful change in a memory clinic cohort. Methods: In the first, qualitative part of the study, community-recruited informal caregivers of patients with ADRD and memory clinic clinicians completed a survey in which they judged various situations representing changes in everyday functioning. Their judgments of meaningful change were used to determine thresholds for MIC, both for decline and improvement, on the Amsterdam Instrumental Activities of Daily Living (IADL) Questionnaire. In the second, quantitative part, we applied these values in an independent longitudinal cohort study of unselected memory clinic patients. Results: MIC thresholds were established at the average threshold of caregivers (N = 1, 629; 62.4 ± 9.5 years; 77% female) and clinicians (N = 13): −2.2 points for clinically meaningful decline and +5.0 points for clinically meaningful improvement. Memory clinic patients (N = 230; 64.3 ± 7.7 years; 39% female; 60% dementia diagnosis) were followed for 1 year, 102 (45%) of whom showed a decline larger than the MIC, after a mean of 6.7 ± 3.5 months. Patients with a dementia diagnosis and more atrophy of the medial temporal lobe had larger odds (odds ratio [OR] = 3.4, 95% CI [1.5–7.8] and OR = 5.0, 95% CI [1.2–20.0], respectively) for passing the MIC threshold for decline than those with subjective cognitive complaints and no atrophy. Discussion: We were able to operationalize clinically meaningful decline in IADL by determining the MIC. The usefulness of the MIC was supported by our findings from the clinical sample that nearly half of a sample of unselected memory clinic patients showed a meaningful decline in less than a year. Disease stage and medial temporal atrophy were predictors of functional decline greater than the MIC. Our findings provide guidance in interpreting changes in IADL and may help evaluate treatment effects and monitor disease progression.